The Disposition of Nature : Environmental Crisis and World Literature - Wenzel, Jennifer (Book collections on Project MUSE., 2019)
This book examines how literature shapes understandings of nature and can therefore be both complicit in environmental harm and part of an environmentalist practice. The book devotes particular attention to formerly colonized regions (e.g. Africa and South Asia) in order to understand the relationships among imperialism, globalization, and environmental injustice.